Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.14744/semb.2021.69851
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Treatment for Multidrug-Resistant Gram-Negative Infections in Children: Caution Required for Nephrotoxicity

Abstract: Objectives Colistin has come to the fore as a treatment option, especially with the occurrence of multidrug-resistant Gram-negative infections across the world. However, the high nephrotoxic effects of colistin should be taken into consideration in children. The study’s primary outcome was to determine the clinical success of the colistin treatment, and the secondary outcome was to detect the side effects related to colistin. Methods The patients who received intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“… 30 , 31 The all-cause 30-day mortality rate in our study was 20.0%, which is comparable to that of a recently published retrospective study that included 21 children with hematologic malignancies infected with a carbapenem-resistant gram-negative organism and treated with ceftazidime-avibactam, and reported an overall mortality rate of 20%. 23 However, the mortality rate of children infected with multidrug-resistant gram-negative organisms and treated with polymyxins in several retrospective reports fluctuated between approximately 30% and 40%, 31–33 which is higher than that observed in our study.…”
Section: Discussionsupporting
confidence: 84%
“… 30 , 31 The all-cause 30-day mortality rate in our study was 20.0%, which is comparable to that of a recently published retrospective study that included 21 children with hematologic malignancies infected with a carbapenem-resistant gram-negative organism and treated with ceftazidime-avibactam, and reported an overall mortality rate of 20%. 23 However, the mortality rate of children infected with multidrug-resistant gram-negative organisms and treated with polymyxins in several retrospective reports fluctuated between approximately 30% and 40%, 31–33 which is higher than that observed in our study.…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that less nephrotoxicity is seen in critically ill children than adults due to the use of colistin. 14 However, clinicians should be careful because of the increasing use of polymyxins in critically ill patients and cases of resistance to this agent.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae is one of the most clinically significant Gram-negative bacteria that causes both community-and hospital-acquired infections, and it is associated with high mortality rates owing to its globally increasing resistance rates to multiple currently available antibiotics including carbapenems [1]. Currently, colistin treatment is considered as a salvage therapy for patients infected with multi-drug-resistant (MDR) Gram-negative bacteria such as K. pneumoniae [2]. MDR is defined as acquired non-susceptibility to at least one agent in three or more antimicrobial categories [3].…”
Section: Introductionmentioning
confidence: 99%